Implementasi Pop Up Book Dalam Meningkatkan Kecerdasan Linguistik Pada Anak Usia Dini - Masganti Sitorus; Annisa Nasution; Astri Syakira Sunya; Mira Sinta Lubis (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research aims to explore the effectiveness of implementing pop up books in improving linguistic intelligence in early childhood at RA Habibilla, Medan City, North Sumatra. Pop-up book media is a three-dimensional and interactive type of media. By using this media, teachers can teach and introduce various kinds of stories to children, which teachers want to tell to children, with multiple themes and stories that are used and told. Using descriptive methods with a qualitative approach, data was collected through observation, interviews and documentation. The collected data was analyzed in depth using the reduction and data display stages. The conclusions were drawn to gain a comprehensive insight into implementing pop-up books to improve linguistic intelligence in early childhood at RA Habibilla.The research results show that the use of pop up books not only increases children's linguistic intelligence but also influences their cognitive, social, emotional, religious and artistic aspects. Children show high enthusiasm, increased vocabulary and better speaking skills. These findings are in line with Vygotsky's theory of language development and Gardner's Multiple Intelligences theory. The conclusion of this research suggests that pop up books are an effective and innovative learning media for developing various aspects of intelligence in early childhood.